Tectorial membrane: structure, function, and its implications for hearing loss - Bian, Panpan; Dang, Jiong; Xu, Bai-cheng (Frontiers in Neurology, 2025)
The tectorial membrane (TM) is an essential extracellular matrix in the cochlea, integral to auditory processing by facilitating hair cell stimulation and sound transmission. Despite its vital role, the mechanisms underlying TM-related hearing loss remain unclear. This review aim to discuss the structure and functions of the TM, exploring its role in cochlear mechanics and auditory signal amplification. Abnormalities in TM composition, including disruptions in collagen, glycosaminoglycans, and non-collagenous proteins, are implicated in various forms of hearing loss, including those associated with genetic mutations and ototoxic drug exposure. We also examine the contributions of genes such as TECTA, TECTB, and CEACAM16, whose mutations disrupt TM integrity and lead to sensorineural hearing loss. Additionally, the impact of aging and thyroid hormone deficiency on TM degeneration is considered. Current diagnostic and therapeutic approaches are discussed, with an emphasis on the potential of gene therapy and stem cell therapy.